Detection of Human Papillomavirus Among Women in Laos: Feasibility of Using Filter Paper Card and Prevalence of High-Risk Types. Issue 8 (1st October 2012) - Phongsavan, Keokedthong; Gustavsson, Inger; Marions, Lena; Phengsavanh, Alongkone; Wahlström, Rolf; Gyllensten, Ulf
Abstract : Background: Persistent infection with high-risk (HR) human papillomavirus (HPV) is a well-recognized cause of cervical cancer, but little is known about the situation in Laos. The aims of the study were to determine the prevalence of HR-HPV among Lao women and to evaluate the use of a filter paper card (FTA Elute Micro Card) for collection of cervical cells in the humid tropical climate. Methods: This is a cross-sectional study including 1922 women from 3 provinces in Laos. During a gynecological examination, cervical cells were collected and applied to the FTA card followed by HPV typing using a real-time polymerase chain reaction (PCR)-based assay. Results: Overall, 213 of the 1922 women were positive for HR-HPV (11%). The most common type was the group HPV33/52/58 (3%), followed by the single type 16 (2%) and the group 18/45 (1%), respectively. Only 11 cards (0.6%) did not contain a sufficient amount of genomic DNA for polymerase chain reaction–based analysis. Conclusions: The prevalence of HR-HPV infections in Laos is similar to other Asian countries, and 40% of the women with an HR-HPV infection will be target of the present HPV vaccines. The FTA card is suitable for collection of cervical cells for HR-HPV typing in tropical conditions. This information is important for planning and establishing primary and secondary prevention of cervical cancer in Laos.